THE IMPLEMENTATION OF THE BEGINNING READING AND WRITING METHOD TO IMPROVE SIMPLE SENTENCE READING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Yunita, Yunita; Syamsuddin, Syamsuddin; Ulfah, Ulfah; Tahir, Moh.; Nuraeni, Ida; Wilade, Surahman (JURNAL KONFIKS, 2025)
This classroom action research aims to improve the ability to read simple sentences in grade 1B students of SDN 2 Tatura in learning Indonesian. The research subjects were 28 students, consisting of 16 males and 12 females. The research was conducted in two cycles using the PTK model which includes the stages of planning, action implementation, observation, and reflection. The main problem in this study is the low ability of students to understand and read simple sentences. As a solution, the Early Reading Writing (MMP) method was applied which is contextual and student-centered. Data were collected through observations of teacher and student activities, as well as learning outcome tests using student worksheets (LKPD). The results of the study showed an increase in the percentage of student learning completion from 75% in cycle I to 93% in cycle II. These findings indicate that the MMP method is effective in improving the ability to read simple sentences of grade 1 students in the context of learning Indonesian